Antimicrobial resistance and genomic characterization of Salmonella enterica isolates from chicken meat - Alzahrani, Khaloud O.; AL-Reshoodi, Fahad M.; Alshdokhi, Elaf A.; Alhamed, Ashwaq S.; Al Hadlaq, Meshari A.; Mujallad, Mohammed I.; Mukhtar, Lenah E.; Alsufyani, Amani T.; Alajlan, Abdullah A.; Al Rashidy, Malfi S.; Al Dawsari, Mashan J.; Al-Akeel, Saleh I.; et al. (Frontiers in Microbiology, 2023)
This study investigated genotypic and phenotypic antimicrobial resistance profiles, phylogenic relatedness, plasmid and virulence composition of 39 Salmonella enterica strains isolated from chicken meat samples using whole genome sequencing (WGS) technology. Four distinct serotypes were identified; Salmonella Minnesota (16/39, 41%), Salmonella Infantis (13/39, 33.3%), Salmonella Enteritidis (9/39, 23.1%), and one isolate was detected for Salmonella Kentucky (1/39, 2.6%), with sequence types (STs) as followed: ST548, ST32, ST11, and ST198, respectively. Phenotypic resistance to tetracycline (91.2%), ampicillin (82.4%), sulfisoxazole (64.7%), and nalidixic acid (61.6%) was the most observed. Resistome analysis revealed the presence of resistance genes to aminoglycosides, beta-lactamase, sulfonamides, trimethoprin, phenicol, lincosamide, macrolides, and tetracyclines. Plasmidome showed the presence of eight incompatibility groups including Col, IncA/C2, IncR, IncX, IncHI, IncFIB, IncFII, and IncI plasmids across the 39 genomes. Three resistance genes; sul2, tetA and blaCMY-2 were predicted to be located on IncA/C2 plasmid in S. Minnesota isolates whereas all S. Infantis isolates were positive to IncFIB(pN55391) plasmid that carry blaCTX-M-65 gene. Eleven Salmonella pathogenicity islands and up to 131 stress and/or virulence genes were identified in the evaluated genomes. Phylogenetic analysis showed 4 phylogroups that were consistent with the identified ST profiles with high level of inter-diversity between isolates. This is the first genomic characterization of Salmonella isolates from retail chicken meat in Saudi Arabia using WGS technology. The availability of Salmonella genomes from multiple geographic locations, including Saudi Arabia would be highly beneficial in future source-tracking, especially during epidemiological surveillance and outbreak investigations.